Homogeneous emission line broadening in the organo lead halide perovskite CH3NH3PbI3-xCl - Wehrenfennig, C; Liu, M; Snaith, H; Johnston, M; Herz, L (American Chemical Society, 2014)
The organic-inorganic hybrid perovskites methylammonium lead iodide (CH3NH3PbI3) and the partially chlorine-substituted mixed halide CH3NH3PbI3-xClx emit strong and broad photoluminescence (PL) around their band gap energy of ∼1.6 eV. However, the nature of the radiative decay channels behind the observed emission and, in particular, the spectral broadening mechanisms are still unclear. Here we investigate these processes for high-quality vapor-deposited films of CH3NH3PbI3-xClx using time- and excitation-energy dependent photoluminescence spectroscopy. We show that the PL spectrum is homogenously broadened with a line width of 103 meV most likely as a consequence of phonon coupling effects. Further analysis reveals that defects or trap states play a minor role in radiative decay channels. In terms of possible lasing applications, the emission spectrum of the perovskite is sufficiently broad to have potential for amplification of light pulses below 100 fs pulse duration.